1992
DOI: 10.3109/13816819209046485
|View full text |Cite
|
Sign up to set email alerts
|

Congenital glaucoma in a child with partial lq duplication and 9p deletion

Abstract: A case of partial duplication of chromosome 1 (1q41-qter) and partial deletion of chromosome 9 (9p24-pter) with infantile congenital glaucoma is reported. The histopathology of the eyes is described. The clinical findings ascribed to trisomy 1q and partial monosomy 9p are summarized and compared to this case. As this is the second report of a patient with monosomy 9p24-pter and congenital glaucoma, it may indicate localization of a gene involved in congenital glaucoma in this region of the human genome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Partial trisomy 1q is a rare [Bartsch et al, ], and band 1q41 is an uncommon breakpoint with only few cases reported mostly combined with partial monosomy of other segments of autosomal chromosomes [Rasmussen et al, ; Verbraak et al, ; Emberger et al, ; Kulikowski et al, ; Kulikowski et al, ]. But, our patient had partial trisomy 1q41 → qter and partial trisomy 9 pter → 9q21.32 resulting from a maternal reciprocal translocation t(1;9)(q41;q21.32).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Partial trisomy 1q is a rare [Bartsch et al, ], and band 1q41 is an uncommon breakpoint with only few cases reported mostly combined with partial monosomy of other segments of autosomal chromosomes [Rasmussen et al, ; Verbraak et al, ; Emberger et al, ; Kulikowski et al, ; Kulikowski et al, ]. But, our patient had partial trisomy 1q41 → qter and partial trisomy 9 pter → 9q21.32 resulting from a maternal reciprocal translocation t(1;9)(q41;q21.32).…”
Section: Discussionmentioning
confidence: 73%
“…But, our patient had partial trisomy 1q41 → qter and partial trisomy 9 pter → 9q21.32 resulting from a maternal reciprocal translocation t(1;9)(q41;q21.32). Among the seven cases of partial trisomy 1q41 → qter reported to date, two were the product of a translocation 1q41 to the short arm of chromosome 9 [Verbraak et al, ; Kulikowski et al, ]. Chromosome band 1q41 translocation to chromosome 9 has been attributed to presence of a genomic fragile site named FRA1H close to bands 1q41 and 1q42.1 [Curatolo et al, ] and the presence of interstitial telomeric sequences (ITs) at 1q41 defined by Azzalin et al [].…”
Section: Discussionmentioning
confidence: 99%
“…Congenital glaucoma and mental retardation can be caused by a number of chromosomal abnormalities including partial trisomy 3q, trisomy 13, partial trisomy 14, trisomy 18, trisomy 21, 7p-, 10p-, 11p-, 13q-, 16p-, 18q-, and Turner syndrome (Verbraak et al, 1992). Gustavson et al, (1991) reported a 15 month old boy with glaucoma and mental retardation.…”
Section: Discussionmentioning
confidence: 98%
“…In this case report, we describe a cryptic chromosomal rearrangement in two cousins similarly affected with partial 9p monosomy and partial 1q trisomy, both originating from a balanced translocation t(1;9) (q44;p24.3) present in both mothers. Although monosomy 9p has been seldom reported (Swinkels et al, 2008), some cases of 1q44 duplication have been described (Lenzini et al, 2009), while reported cases with both alterations, partial monosomy 9p and partial trisomy 1q are even rarer (Verbraak et al, 1992;Kulikowski et al, 2008).…”
Section: Introductionmentioning
confidence: 99%